Significant Electoral Year for Poland. Analytical Report on the Results of Presidential and Parliament Elections in the Country (in Russian) / A. Martynov, A. Krylov, Mateuz Piskorski, Justyna Jarmutowicz. – Moscow: Mezhdunarodnyi Institut Noveishikh Gosu - Editorial article (Сравнительная политика)
.